2018
DOI: 10.3390/ma11071249
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed Low-Cost Dielectric-Resonator-Based Ultra-Broadband Microwave Absorber Using Carbon-Loaded Acrylonitrile Butadiene Styrene Polymer

Abstract: In this study, an ultra-broadband dielectric-resonator-based absorber for microwave absorption is numerically and experimentally investigated. The designed absorber is made of the carbon-loaded Acrylonitrile Butadiene Styrene (ABS) polymer and fabricated using the 3D printing technology based on fused deposition modeling with a quite low cost. Profiting from the fundamental dielectric resonator (DR) mode, the higher order DR mode and the grating mode of the dielectric resonator, the absorber shows an absorptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
51
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 75 publications
0
51
0
2
Order By: Relevance
“…Lately, 3D printing systems have been utilized to manufacture metamaterial absorbers (MMAs) of different structural designs and material bases [11][12][13][14][15][16][17]. However, the main hindrance for the fabrication of broadband MMAs using 3D printing technology is the limited range of materials compatible with 3D printers [18,19]. Most of the available 3D printing materials are fully insulating or have low conductivity values [11], which limits their usage in 3D printing of EM absorbing metamaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, 3D printing systems have been utilized to manufacture metamaterial absorbers (MMAs) of different structural designs and material bases [11][12][13][14][15][16][17]. However, the main hindrance for the fabrication of broadband MMAs using 3D printing technology is the limited range of materials compatible with 3D printers [18,19]. Most of the available 3D printing materials are fully insulating or have low conductivity values [11], which limits their usage in 3D printing of EM absorbing metamaterials.…”
Section: Introductionmentioning
confidence: 99%
“…AM have been employed for development of antennas for various applications including antennas for 5G systems. AM can be used to print metallic structures [20], dielectric layers [21] or both layers [22] of an antenna. Dielectric lenses [23] and dielectric resonator antennas [24] are example of dielectric only printed antennas.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, extensive study of absorbers has revealed that an array of the absorbers could modify the effective material properties with narrow absorption bandwidths. Therefore, diverse techniques and designs have been proposed to enhance the bandwidths, such as modifying the resonator structure, lumped elements resonators, layered structure, and frequency selective surface (FSS), among others 4 7 . High absorption and narrowband responses can clarify some design variations with a closed-ring shape, octagonal shape, resistive-load imposing, and some ring variations 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%